2017
DOI: 10.1080/15384101.2016.1220461
|View full text |Cite
|
Sign up to set email alerts
|

Cell-cycle-dependent drug-resistant quiescent cancer cells induce tumor angiogenesis after chemotherapy as visualized by real-time FUCCI imaging

Abstract: We previously demonstrated that quiescent cancer cells in a tumor are resistant to conventional chemotherapy as visualized with a fluorescence ubiquitination cell cycle indicator (FUCCI). We also showed that proliferating cancer cells exist in a tumor only near nascent vessels or on the tumor surface as visualized with FUCCI and green fluorescent protein (GFP)-expressing tumor vessels. In the present study, we show the relationship between cellcycle phase and chemotherapy-induced tumor angiogenesis using in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 16 publications
(14 reference statements)
1
30
0
Order By: Relevance
“…4C]. As previously reported, cell cycle disorder is an important mechanism underlying the increased malignancy of tumor cells (22) , and alterations in the cell cycle have been considered responsible for drug resistance (23) . Therefore, we propose that loss of control of the G1/S transition may explain why PSTT is resistant to MTX in vivo and in vitro compared to MTX-sensitive choriocarcinoma cell lines.…”
Section: Results 4g1 Phrase Arrest and G1/s-phrase Transition Was Dysrmentioning
confidence: 95%
See 1 more Smart Citation
“…4C]. As previously reported, cell cycle disorder is an important mechanism underlying the increased malignancy of tumor cells (22) , and alterations in the cell cycle have been considered responsible for drug resistance (23) . Therefore, we propose that loss of control of the G1/S transition may explain why PSTT is resistant to MTX in vivo and in vitro compared to MTX-sensitive choriocarcinoma cell lines.…”
Section: Results 4g1 Phrase Arrest and G1/s-phrase Transition Was Dysrmentioning
confidence: 95%
“…Defective cell cycle events result in uncontrolled cell proliferation, which is considered as one of the hallmarks of cancer (22) . Oncogenic processes exhibit their greatest effects by targeting G1 phase progression (15) and alternations in cell cycle have also been considered responsible for drug resistance (23) . Many studies have verified that cell cycle disorders are related to MTX-resistant in some solid tumors (36,37) , therefore, we decided to focus our study of MTX-resistance on dysregulated cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle includes G 0 /G1 phase (DNA presynthetic phase), S phase (DNA synthesis phase), and G2/M phase (DNA postsynthetic and mitosis phases) (Yano et al, ). Different from ours, Zhang et al () showed that extracts of fermented wheat germ attenuated the progression in the G0/G1 phase, same with Anduix's (Comín‐Anduix et al, ) finding which revealed that fermented extract of wheat germ halted in the S cycle phase while there was a notable accumulation of the G0/G1 cycle phase.…”
Section: Discussionmentioning
confidence: 99%
“…5; Ki67 column). This impartial cancer cell targeting is clearly advantageous over the effect of various FDAapproved anticancer drugs that mainly target proliferating cells [40,41,73,74] .…”
Section: Structure-activity Relationship Studymentioning
confidence: 99%